Is Lymph Node Dissection Necessary During Radical Nephroureterectomy for Clinically Node-Negative Upper Tract Urothelial Carcinoma? A Multi-Institutional Study - Lee, Hsiang-Ying; Chang, Chao-Hsiang; Huang, Chi-Ping; Yu, Chih-Chin; Lo, Chi-Wen; Chung, Shiu-Dong; Wu, Wei-Che; Chen, I-Hsuan Alan; Lin, Jen-Tai; Jiang, Yuan-Hong; Lee, Yu-Khun; Hsueh, Thomas Y.; et al. (Frontiers in Oncology, 2022)
Purpose: This study aimed to compare the oncological outcomes of patients with upper tract urothelial carcinoma (UTUC) without clinical lymph node metastasis (cN0) undergoing lymph node dissection (LND) during radical nephroureterectomy (NU). Methods: From the updated data of the Taiwan UTUC Collaboration Group, a total of 2726 UTUC patients were identified. We only include patients with ≥ pT2 stage and enrolled 658 patients. The Kaplan–Meier estimator and Cox proportional hazards model were used to analyze overall survival (OS), cancer-specific survival (CSS), disease-free survival (DFS), and bladder recurrence-free survival (BRFS) in LND (+) and LND (−) groups. Results: A total of 658 patients were included and 463 patients without receiving LND and 195 patients receiving LND. From both univariate and multivariate survival analysis, there are no significant difference between LND (+) and LND (-) group in survival rate. In LND (+) group, 18.5% patients have pathological LN metastasis. After analyzing pN+ subgroup, it revealed worse CSS (p = 0.010) and DFS (p < 0.001) compared with pN0 patients. Conclusions: We found no significant survival benefit related to LND in cN0 stage, ≥ pT2 stage UTUC, irrespective of the number of LNs removed, although pN+ affected cancer prognosis. However, from the result of pN (+) subgroup of LND (+) cohort analysis, it may be reasonable to not perform LND in patients with cT2N0 stage due to low positive predictive value of pN (+). In addition, performing LND may be considered for ureter cancer, which tends to cause lymphatic and hematogenous tumor spreading. Further large prospective studies are needed to validate our findings.